IMPROVING STUDENTS MOTIVATION AND LEARNING ACTIVITY THROUGH INTERACTIVE MEDIA IN CLASS III SDN PETOK - Rizan Zakiyya; Agung Setyawan (Citra Dharma Cindekia, 2022)
One of the characteristics of students who have high learning motivation is active in learning activities. This is one indicator that learning can be said to be meaningful. One way to increase students motivation and activeness in learning is to use interactive media. The purpose of this study was to determine whether the use of interactive media can increase the motivation and activity of third grade students at SDN Petok. This study uses data collection techniques in the form of interviews, observations, tests, and documentation. The data was then analyzed using qualitative data analysis techniques. The results of this study indicate that there is an increase in student activity based on the results of observations made by researchers. Until the end of the second cycle, all students from the front to the back seemed active and enthusiastic about the material presented by the researcher. All students look serious in discussion activities and when working on group assignments. In addition, there were some students who actively asked questions when they found material they did not understand and were responsive in answering several questions from the teacher. Based on the results of the study, it can be concluded that interactive learning media can increase students motivation and activeness in learning